Error Correction Strategies and Writing Competency of Senior High School Students - Navarro, Ana Louella; Caballo, John Harry; Ngo, Cristy Grace (Research Parks Publishing LLC, 2025)
This study aimed to unravel the relationship between error correction strategies and writing competency of students. There were 120 Humanities and Social Sciences senior high school students from three different schools in Davao City who were chosen as respondents using a purposive sampling technique. The students were asked to write a 10-sentence essay, 60 of which were corrected using Selective Direct Feedback and the other half with Selective Indirect Feedback. The researcher sought help from interraters who used a 5-point rubric in checking three areas of grammar: subject-verb agreement, tenses, and connectives. Three statistical tools were used: Mean Scores, T-test for dependent samples, and T-test for independent samples. Results revealed that before the use of the two strategies in the first set of output there were several errors in the written outputs, In the second set, after the use of the Selective Direct Feedback and Selective Indirect Feedback, there were fewer errors found in the essay. However, the reductions in errors were not significantly different between the two feedback methods.